Activation of the rostromedial prefrontal cortex during the experience of positive emotion in the context of esthetic experience. An fNIRS study - Kreplin, Ute; Fairclough, Stephen H. (Frontiers in Human Neuroscience, 2013)
The contemplation of visual art requires attention to be directed to external stimulus properties and internally generated thoughts. It has been proposed that the medial rostral prefrontal cortex (rPFC; BA10) plays a role in the maintenance of attention on external stimuli whereas the lateral area of the rPFC is associated with the preservation of attention on internal cognitions. An alternative hypothesis associates activation of medial rPFC with internal cognitions related to the self during emotion regulation. The aim of the current study was to differentiate activation within rPFC using functional near infrared spectroscopy (fNIRS) during the viewing of visual art selected to induce positive and negative valence, which were viewed under two conditions: (1) emotional introspection and (2) external object identification. Thirty participants (15 female) were recruited. Sixteen pre-rated images that represented either positive or negative valence were selected from an existing database of visual art. In one condition, participants were directed to engage in emotional introspection during picture viewing. The second condition involved a spot-the-difference task where participants compared two almost identical images, a viewing strategy that directed attention to external properties of the stimuli. The analysis revealed a significant increase of oxygenated blood in the medial rPFC during viewing of positive images compared to negative images. This finding suggests that the rPFC is involved during positive evaluations of visual art that may be related to judgment of pleasantness or attraction. The fNIRS data revealed no significant main effect between the two viewing conditions, which seemed to indicate that the emotional impact of the stimuli remained unaffected by the two viewing conditions.